2018
DOI: 10.1159/000481667
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Behavioural and Sociodemographic Risk Indicators on Erosive Tooth Wear in Flemish Adolescents, Belgium

Abstract: Although Belgium has recently been ranked as the second highest consumer of soft drinks in Europe, no data on erosive tooth wear (ETW) are currently available. Therefore, the aim of this cross-sectional study was to determine the prevalence and associated risk indicators of ETW in adolescents residing in the region of Flanders, Belgium. Convenience sampling was used to recruit participants from different types of Belgian schools: general and vocational/technical education. Three calibrated dentists performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
(69 reference statements)
0
11
0
Order By: Relevance
“…Our previous findings suggested the existence of a possible link between school type, consumption of soft drinks and prevalence of ETW in Belgium [11]. The need to clarify this correlation motivated the present study, which is the first in its kind investigating the SFP related to acidic beverage consumption.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our previous findings suggested the existence of a possible link between school type, consumption of soft drinks and prevalence of ETW in Belgium [11]. The need to clarify this correlation motivated the present study, which is the first in its kind investigating the SFP related to acidic beverage consumption.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study of ETW in Belgium showed that type of education (vocational/technical) was a predictive variable for ETW risk in adolescents (odds ratio (OR): 1.49; 95% CI: 1.03–2.13). A higher prevalence of ETW was shown in students registered to vocational/technical schools (VSE) where a significantly higher intake of acidic beverages occurred and a lower socioeconomic status (SES) was present [11]. This link between education type, SES, and level of soft drink consumption was similarly shown in Norway by Mulic et al 2012 [13].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…These findings are in accordance with those by Kanzow et al [13], who reported that dentists who followed continuous education courses dealing with erosive tooth wear were able to detect lesions in enamel more frequently than dentists who had not participated in any course. In the context of the Belgian practicing dentists, the early diagnosis of erosive tooth wear is of relevance due to its high prevalence in adolescents [27]. Conversely, distinct defects of erosive tooth wear were easily detected by most of the dentists, as observed by Kanzow et al [13].…”
Section: Discussionmentioning
confidence: 99%